ST IES ON LENG IGHT RELATIONSHIPS OF GERRES FILAMENTOSUS CUVIER FROM THE ESTU IES OF T I SOUTHEKN r:ARNAT COAST* - Udupa, K. S.; Averel, M.; Raghavendra, C. H.; Bevinahalli, Vinayak; Reddy, Ashwath; Kumarswamy, A. R. (Journal of Indian Fisheries Association, 2016)
Random samples of Gerres filamentosus Cuvier from the Netravathi-Gurpur, Mulky, Kallayanapura, Mabukala and Kundapura estuaries of thesouthern Karnataka Coast were collected in the years 2000, 2001 and 2002,and length-weight relationships for each estuary were derived using multiplelinear regression technique with one dummy variable. Hence, combined orsex-wise length-weight relationships were obtained after testing forhomogeneity and isometric growth condition of fishes for each estuary by ttest.The extent of closeness of length-weight relationships between sexesand among estuaries for different years is explained by a trend line graph.The whole process of multiple linear regression analysis with one dummyvariable is a better substitute for the analysis of covariance technique.Keywords: Gerres filamentosus, estuaries, length-weight relationships,multiple linear regression technique